The Persistence of National Victimhood: Bosniak Post-War Memory Politics of the Srebrenica Mass Killings - Tomasz Rawski (Sprawy Narodowościowe. Seria nowa, 2021)
The Persistence of National Victimhood: Bosniak Post-War Memory Politics of the Srebrenica Mass Killings